Enriching the earth : Fritz Haber, Carl Bosch, and the transformation of world food production - Smil, Vaclav (Cambridge, Mass. ; London : MIT, 2004)
The industrial synthesis of ammonia from nitrogen and hydrogen, making possible artificial fertilizers, was of fundamental importance to the modern world. The expansion of the world's population from 1.6 billion people in 1900 to today's six billion would not have been possible without the synthesis of ammonia. The book begins with a discussion of nitrogen's unique status in the biosphere, its role in crop production, and traditional means of supplying the nutrient. He then looks at various attempts to expand natural nitrogen flows through mineral and synthetic fertilizers. The core of the book is a detailed narrative of the discovery of ammonia synthesis by Fritz Haber and its commercialization by Carl Bosch and the chemical company BASF.
Nitrogen in agriculture : discovering the basics -- Traditional sources of nitrogen : preindustrial agricultures -- New sources of the nutrient : searching for fixed nitrogen -- A brilliant discovery : Fritz Haber's synthesis of ammonia -- Creating an industry : Carl Bosch and BASF -- Evolution of ammonia synthesis : diffusion and innovation -- Synthetic fertilizers : varieties and applications -- Our dependence on nitrogen : agricultures and populations -- Consequences of the dependence : human interference in nitrogen's biospheric cycle -- Nitrogen and civilization : managing the nitrogen cycle.
Originally published: 2000.
Includes bibliographical references and index.
Keywords: Nitrogen fertilizers; Ammonia as fertilizer